2022
DOI: 10.2147/dmso.s370158
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metabolomics in Various Types of Diabetes

Abstract: Metabolomics is the analysis of numerous small molecules known as metabolites. Over the past few years, with the continuous development in metabolomics, it has been widely used in the detection, diagnosis, and treatment of diabetes and has demonstrated great benefits. At the same time, studies on diabetes and its complications have discovered the metabolic markers that are characteristic of diabetes. However, the pathogenesis of diabetes has yet to be clarified, as well as no complete cure. The mechanism of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…With the rapid rise in metabolomics, the combination of metabolomics detection technology with computational biology and orthogonal experiments can help screen diabetes-related metabolites and infer metabolic pathways. 12 The results showed that HUVECs affected ve metabolic pathways, including starch and sucrose metabolism, amino sugar and nucleotide sugar metabolism, fructose and mannose metabolism, histidine metabolism, and galactose metabolism, within 48 h after burn. Among these, starch and sucrose metabolism and histidine metabolism had the greatest impact.…”
Section: Discussionmentioning
confidence: 93%
“…With the rapid rise in metabolomics, the combination of metabolomics detection technology with computational biology and orthogonal experiments can help screen diabetes-related metabolites and infer metabolic pathways. 12 The results showed that HUVECs affected ve metabolic pathways, including starch and sucrose metabolism, amino sugar and nucleotide sugar metabolism, fructose and mannose metabolism, histidine metabolism, and galactose metabolism, within 48 h after burn. Among these, starch and sucrose metabolism and histidine metabolism had the greatest impact.…”
Section: Discussionmentioning
confidence: 93%
“…Since metabolites reflect the whole body’s functions, it is hypothesised that they can provide a comprehensive picture of what happens in the body. The combination of metabolomics detection technology with computational biology and orthogonal experiments allows the screening of diabetic metabolites and evaluation of the related metabolic pathways[ 128 ]. Evidently, through metabolomics research, it is discovered that T1DM children who developed auto-antibodies before the age of 2 had twice the depletion rate of methionine level compared to the children who developed autoantibodies in later childhood or children who were auto-antibody-negative.…”
Section: Future Direction In Management Of Diabetic Neuropathymentioning
confidence: 99%
“…Hyperglycemia can confirm the presence of diabetes in individuals and can also predict the progression of the disease or the likelihood of complications. 14 However, metabolic dysfunction associated with the development of diabetes may manifest before an increase in the blood glucose levels. Liu et al found that the levels of choline-related lipids (including phosphatidylcholines, sphingomyelins, and lysophosphatidylcholines) significantly changed with the progression of T1D.…”
Section: ■ Introductionmentioning
confidence: 99%